Audio-Visual Media in Differentiated Economics Instruction: Effects on Students' Critical and Creative Thinking - Muhammad Irsan; Husamah; Arina Restian (Women, Education, and Social Welfare, 2026)
Developing higher-order thinking through equitable learning design remains a challenge in secondary economics education. This quasi-experimental study tested whether audio-visual media embedded in differentiated instruction improved critical and creative thinking among eleventh-grade students at State Islamic Senior High School (Madrasah Aliyah Negeri [MAN]) 3 Mataram, Indonesia. Two intact classes (N = 60) participated in a non-equivalent pretest-posttest control-group design. The experimental class received six 90-minute sessions integrating video, animation, infographics, economic cases, flexible learning processes, and product choice; the control class received conventional instruction. Critical-thinking essays and a creative poster project were scored using validated rubrics. MANCOVA, controlling for both pretests, showed a significant multivariate instructional effect, Pillai's Trace = .400, F(2, 55) = 18.303, p < .001, partial eta squared = .400. Univariate effects favored the experimental group for critical thinking, F(1, 56) = 5.662, p = .021, partial eta squared = .092, and creative thinking, F(1, 56) = 32.118, p < .001, partial eta squared = .364. The findings indicate that accessible multimodal resources coupled with differentiated learning pathways can strengthen higher-order thinking, particularly creative problem solving in unemployment-related economic cases.